Upper thermal limits and risk of mortality of coastal Antarctic ectotherms - Carter, Mauricio J.; García-Huidobro, M. Roberto; Aldana, Marcela; Rezende, Enrico L.; Bozinovic, Francisco; Galbán-Malagón, Cristóbal; Pulgar, José M. (Frontiers in Marine Science, 2023)
Antarctic marine animals face one of the most extreme thermal environments, characterized by a stable and narrow range of low seawater temperatures. At the same time, the Antarctic marine ecosystems are threatened by accelerated global warming. Determining the upper thermal limits (CTmax) is crucial to project the persistence and distribution areas of the Antarctic marine species. Using thermal death time curves (TDT), we estimated CTmax at different temporal scales from 1 minute to daily and seasonal, the predict vulnerability to the current thermal variation and two potential heatwave scenarios. Our results revealed that CTmax at 1 min are far from the temperature present in the marine intertidal area where our study species, showing Echinoderm species higher CTmax than the Chordata and Arthropods species. Simulations indicated that seasonal thermal variation from the intertidal zone contributed to basal mortality, which increased after considering moderate scenarios of heatwaves (+2°C) in the Shetland Archipelago intertidal zone. Our finding highlighted the relevance of including exposure time explicitly on the CTmax estimates, which deliver closer and more realistic parameters according to the species that may be experiencing in the field.